Planning a trail using landowner preferences: a multivariable least-cost path approach - Whitehouse, Caleb Douglas (Kansas State University, 2021)
Recreational trails provide a valuable asset for communities, especially in rural areas. However, some adjacent landowners have serious concerns about the impact that a proposed trail and its users may have on their lives and property. While the least-cost path has been used to create recreational trails before, it has not been demonstrated in an area dominated by private property. This report seeks to create a tool that planners can use to create trails using a multivariate analysis. Landowner concerns and preferences for a trails route have been incorporated into a least-cost path model in addition to the preferences of trail users and taxpayers. The resulting paths provide a look at what a trail could look like, and how different variables alter its route and costs. Additionally, the feedback from the interviews with landowners will add to the existing literature of landowner attitudes about recreational trails.
Keywords: Planning; Trail; Recreational trail; Landowner preferences; Least-cost path; GIS